Reduced Dnmt3a increases Gdf5 expression with suppressed satellite cell differentiation and impaired skeletal muscle regeneration. Issue 3 (3rd January 2018) - Hatazawa, Yukino; Ono, Yusuke; Hirose, Yuma; Kanai, Sayaka; Fujii, Nobuharu L.; Machida, Shuichi; Nishino, Ichizo; Shimizu, Takahiko; Okano, Masaki; Kamei, Yasutomi; Ogawa, Yoshihiro
Abstract : DNA methylation is an epigenetic mechanism regulating gene expression. In this study, we observed that DNA methyltransferase 3a (Dnmt3a) expression is decreased after muscle atrophy. We made skeletal muscle‐specific Dnmt3a‐knockout (Dnmt3a‐KO) mice. The regeneration capacity after muscle injury was markedly decreased in Dnmt3a‐KO mice. Diminished mRNA and protein expression of Dnmt3a were observed in skeletal muscles as well as in satellite cells, which are important for muscle regeneration, in Dnmt3a‐KO mice. Dnmt3a‐KO satellite cell showed smaller in size (length/area), suggesting suppressed myotube differentiation. Microarray analysis of satellite cells showed that expression of growth differentiation factor 5 (Gdf5) mRNA was markedly increased in Dnmt3a‐KO mice. The DNA methylation level of the Gdf5 promoter was markedly decreased in Dnmt3a‐KO satellite cells. In addition, DNA methylation inhibitor azacytidine treatment increased Gdf5 expression in wild‐type satellite cells, suggesting Gdf5 expression is regulated by DNA methylation. Also, we observed increased inhibitor of differentiation (a target of Gdf5) mRNA expression in Dnmt3a‐KO satellite cells. Thus, Dnmt3a appears to regulate satellite cell differentiation via DNA methylation. This mechanism may play a role in the decreased regeneration capacity during atrophy such as in aged sarcopenia.—Hatazawa, Y., Ono, Y., Hirose, Y., Kanai, S., Fujii, N. L., Machida, S., Nishino, I., Shimizu, T., Okano, M., Kamei, Y., Ogawa, Y. Reduced Dnmt3a increases Gdf5 expression with suppressed satellite cell differentiation and impaired skeletal muscle regeneration. FASEB J. 32, 1452‐1467 (2018). www.fasebj.org